Penentuan Rute Transportasi Kendaraan Umum Kota Medan Dengan Menggunakan Nearest Neighbor Method Dan Closed Insertion Method - Putra, Fani Darmawan; Rakhmawati, Fibri; Cipta, Hendra (Zeta - Math Journal, 2021)
ABSTRACT The purpose of this research to arrange the route of the Medan public transportation system into a graph and find the closest route using a graph. The data used are data on travel routes and travel times public transportation for Terminal Pinang Baris to Terminal Amplas. The results obtained are Medan City Public Transport system namely KPUM 64, RMC 120 and U-MORINA 138 can be represented in graph with terminal as a vertex and the walk to connecting each terminal as edge. The calculation results using the nearest neighbor method and closed insertion method can produce different routes between KPUM 48, RMC 120 and U-MORINA 138 which have been operating now. Determining the shortest route by considering the shortest distance does not get jammed. Keywords: Public Transportation, Routing Graph, Nearest Neighbor Method, Closed Insertion Method.